Ultra-low-voltage CMOS-based current bleeding mixer with high LO-RF isolation - Tan, Gim Heng; Mohd Sidek, Roslina; Ramiah, Harikrishnan; Chong, Wei Keat; Lioe, De Xing (Hindawi Publishing Corporation, 2014)
This journal presents an ultra-low-voltage current bleeding mixer with high LO-RF port-to-port isolation, implemented on 0.13 μm standard CMOS technology for ZigBee application. The architecture compliments a modified current bleeding topology, consisting of NMOS-based current bleeding transistor, PMOS-based switching stage, and integrated inductors achieving low-voltage operation and high LO-RF isolation. The mixer exhibits a conversion gain of 7.5 dB at the radio frequency (RF) of 2.4 GHz, an input third-order intercept point (IIP3) of 1 dBm, and a LO-RF isolation measured to 60 dB. The DC power consumption is 572 µW at supply voltage of 0.45 V, while consuming a chip area of 0.97 × 0.88 mm2.